2022
DOI: 10.1111/ecc.13726
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of unmet supportive care needs of cancer survivors in Australia: A qualitative systematic review

Abstract: Introduction: Cancer incidence and survivorship are increasing worldwide. With more people living through and beyond cancer, there is a subsequent increase in their supportive care needs. This systematic review of qualitative studies aimed to describe the impacts of unmet supportive care needs on cancer survivors in Australia.Methods: Databases MEDLINE, EMBASE and Scopus were searched, and after screening and applying eligibility criteria, 27 qualitative studies were included. Findings were synthesised accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 83 publications
0
13
0
Order By: Relevance
“…Numerous studies have demonstrated the existence of a range of unmet needs throughout the entire cancer journey and the negative impact such unmet issues have on the lives of patients and their families [26,28,29]. Although specific unmet needs can differ among cancer types [28], the breadth of issues across all domains (i.e., physical, psychological, social, spiritual, informational, and practical) is common to all cancers [26,28,29]. The principles of supportive care involve addressing all such unmet needs, through ongoing holistic assessment and appropriate interventions from relevant members of the extended supportive care team.…”
Section: Rationale and Evidence For Supportive Carementioning
confidence: 99%
“…Numerous studies have demonstrated the existence of a range of unmet needs throughout the entire cancer journey and the negative impact such unmet issues have on the lives of patients and their families [26,28,29]. Although specific unmet needs can differ among cancer types [28], the breadth of issues across all domains (i.e., physical, psychological, social, spiritual, informational, and practical) is common to all cancers [26,28,29]. The principles of supportive care involve addressing all such unmet needs, through ongoing holistic assessment and appropriate interventions from relevant members of the extended supportive care team.…”
Section: Rationale and Evidence For Supportive Carementioning
confidence: 99%
“…8,9 A systematic review found that patients with higher unmet needs have more severe emotional and psychological problems, such as depression, anxiety, feelings of fear, isolation, and abandonment. 10 In addition, higher unmet needs have been associated with poorer health and a worse quality of life. 4,11 Previous research has examined the risk factors of unmet needs by mainly focusing on the sociodemographic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Studies across various countries and cultures have shown that individuals with cancer reported moderate to high levels of unmet needs—particularly in the psychological, health system and information (HSI), and sexual domains in Western countries and Asian countries such as Japan, 6 South Korea, 7 and China 8,9 . A systematic review found that patients with higher unmet needs have more severe emotional and psychological problems, such as depression, anxiety, feelings of fear, isolation, and abandonment 10 . In addition, higher unmet needs have been associated with poorer health and a worse quality of life 4,11 …”
Section: Introductionmentioning
confidence: 99%
“…Despite these recommendations, a substantial proportion of cancer survivors in Australia report unmet needs in terms of the information they receive to assist them in dealing with their cancer and its sequalae 4 . Further, a recent systematic review has identified that unmet information needs negatively affected cancer survivors' emotional and psychological wellbeing, leaving them feeling isolated, distressed, confused, regretful and abandoned 7 . Previous research has also identified that if post‐treatment information needs are not met in healthcare settings, cancer survivors look elsewhere for this information, particularly from online or interpersonal sources that may not be credible or accurate 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…4 Further, a recent systematic review has identified that unmet information needs negatively affected cancer survivors' emotional and psychological wellbeing, leaving them feeling isolated, distressed, confused, regretful and abandoned. 7 Previous research has also identified that if post-treatment information needs are not met in healthcare settings, cancer survivors look elsewhere for this information, particularly from online or interpersonal sources that may not be credible or accurate. 8,9 For example, 30%-40% of rural cancer survivors and their caregivers report referring to online sources from support.…”
Section: Introductionmentioning
confidence: 99%